Letramento midiático e informacional em meio a pandemia da Covid-19: um estudo dos moradores do bairro Cidade Aracy - Silva Neto, José Marcos Amorim da (Universidade Federal de São Carlos, 2021)
Since the first case of COVID-19 was registered in the city of Wuhan in China at the end of 2019, the disease caused by the coronavirus SARS-Cov-2, has quickly spread across the continents, causing not only a health crisis, but also a “disinformation infodemic”. As this is a new disease, information is essential for self-protection, to be well and to prevent the proliferation of the virus, but it is necessary to recognize the sources of information determined to make good use of truthful information. This study aimed to identify whether the media and information literacy of the residents of the Cidade Aracy neighbourhood, in São Carlos, is related to the evolution of COVID-19 in that neighbourhood. Through a questionnaire addressed to residents, it was possible to identify the behaviour, points of view and habits of the community regarding information about COVID-19. Data show that City Aracy is the most affected by COVID-19, so it was selected for the study. We identified that the participants affirm that they do not have the habit of sharing information about COVID-19 and the vast majority report that they can verify the veracity of information. Therefore, it is possible to conclude that these media and information literacy skills self-reported by the residents, were possibly not related to such alarming numbers of COVID-19 infection in this neighbourhood.
Media and information literacy in the midst of the Covid-19 pandemic: a study of residents of Aracy City neighborhood
Keywords: Letramento midiático e informacional; Fontes de informação; COVID-19; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::PROCESSOS DE DISSEMINACAO DA INFORMACAO